Coleta seletiva de recicláveis: o protagonismo dos catadores na gestão de resíduos sólidos urbanos em Uberaba-MG - Silva, Mauro Cristiano de Paula (2020)
The subject discussed here is remarkably complex and multifaceted, in addition to being present in multiple and controversial approaches for all tastes. The goal of this dissertation is to develop a geographical approach expressed not only through the presentation of maps on selective collection in Uberaba-MG, an urban scenario for the collection of recyclables, but based on an analysis that privileges three fundamental aspects: work relationships of recyclable waste collectors; the territorial characterization of selective collection activities; and state social policies. Based on these three central elements, an attempt was made to develop an approach that evidenced the link between the geographical space and the practices of consumption and disposability that in turn generate the disputes, fueled by precariousness and perversities among those “up against those of low". The socio-spatial dynamics practiced by the first two are enhanced by the third. The State policy of greatest interest to waste collectors is the National Solid Waste Policy (PNRS). Its precepts are gradually being introduced in the integrated management of solid waste of the municipalities with the insertion of the category of recyclable material collectors. Observing these elements, one understands the potential of strategic construction for all the collectors so that their economic practices aim at more than daily survival and gain new perspectives in the possibility of appropriating the territory and mitigating their condition of being excluded, exiled or deterritorialized, for reasons historically built on the deepening of social and class inequalities and on the precariousness of work, currently in multiple sectors of the Brazilian economy where there are workers. This dissertation has in its scope the term “Productive Spatial Circuit of Recyclables” (CEPR) to designate the territory in dispute by the big public cleaning companies, by the collectors and by the owners of deposits. This dispute is latent between the actors directly involved in the appropriation of the territory and recyclable materials. Equally latent among the actors are disputes over state support and contradictions in state permissiveness, which generally ends up benefiting waste businessmen and harming waste collectors. Theoretically: we strived to align the precepts of the work category with the geographical reasoning and the territorial concepts of Santos with the universe of recyclable solid waste; the problem of refuse is approached through an analysis of the mismatched statistics, above all, by the data sources available in Brazil, which makes us understand the challenges to organize integrated waste management; and with the aid of maps and semi-structured interviews, a descriptive and analytical section of the selective collection activities in Uberaba-MG was developed. It was conclusively noted that at present, waste collectors are neglected by State policies and that their work dynamics, although permeated by fluctuating precariousness, have a certain impact on the society of Uberaba by the more than 35 neighborhoods served by selective collection. The territorial formation and the way that this individual settles down in space is what guarantees food, the payment of bills, addictions and the medicines they need. In this territory, waste pickers print their workforce in search of survival and dignity.